Malaysian secondary boarding school menu planning system / Suliadi F. Sufahani and Anuar M. Yusof - Sufahani, Suliadi Firdaus; Mohd Yusof, Anuar (2021)
Boarding school students need to eat well balanced nutritious food which include proper calorie, vitality, and supplements for legitimate development, keeping in mind the end goal is to repair and support the body tissues and averting undesired ailments and disease. Serving healthier menu is a noteworthy stride towards accomplishing that goal. Arranging a nutritious and adjusted menu physically is confounded, wasteful and tedious. This study intends to build up a scientific mathematical model and decision support system for menu planning that improves and meets the vital supplement consumption for boarding school students aged 13-18 and in addition, saving the financial cost. It gives the adaptability and flexibility for the cook to change any favoured menu even after the ideal arrangement has been produced. A recalculation procedure was performed in view of the ideal arrangement. The data were gathered from the Ministry of Education and boarding schools' authorities. Menu arranging is a notable enhancement issue and one of the well-established problems in optimisation. A well-balanced menu scheduling is produced which meets all the constraints. The model was fathomed by utilising Binary Programming and "Sufahani-Ismail Algorithm" and a system was developed to comply with the problem. The Malaysian Secondary Boarding School Menu Planning System is the first system in Malaysia and in the world. It can also be used for other problems such as military, hospitals and others.